Impact of Using Facemasks on Literacy Learning: The Perception of Early Childhood Education Teachers - Diego Vergara; Álvaro Antón-Sancho; Juan-José Maldonado; María Nieto-Sobrino (MDPI AG, 2022)
In this work, quantitative research is carried out on the importance that educators give to literacy work in early childhood education classrooms and the impact that the COVID-19 pandemic and the use of facemasks have had on it. To this end, a survey designed for this purpose has been used, which has been passed on to a set of 112 Spanish early childhood educators. The teachers surveyed occupy different positions in the classroom (tutors, support technicians, specialists in bilingualism, therapeutic pedagogy and speech and hearing), and, in addition, they themselves learned to read from different methods of literacy learning (synthetic or analytical). The results found in this study indicate that educators express intermediate evaluations of the importance of literacy work in the classroom, higher if it is done through digital resources, and higher for the synthetic method than for the analytical method. In addition, the impact of the use of masks on literacy learning was rated as very negative. On the other hand, gaps have been identified in the above perceptions by the position occupied in the classroom and by the method used to learn to read. Finally, some actions are suggested to homogenize the perceptions of the different professionals, and some lines of research are proposed.